Using citizen science to better understand Risso’s dolphin (Grampus griseus) presence in northeast Scotland and the Northern Isles - Hodgins, Nicola K.; Steel, Emma M.; Dyke, Katie; Walters, Alice E. M.; Dolman, Sarah J.; Hall, Karen; Neave-Webb, Emma; Evans, Peter G. H.; Bird, Colin; Robinson, Kevin P.; Marwood, Eleanor M.; Foubister, Robert; et al. (Frontiers in Conservation Science, 2024)
There is no current population estimate for Risso’s dolphin (Grampus griseus) in Scottish waters and their distribution in the northeast of Scotland and the Northern Isles is poorly documented. Using a combination of citizen science and historical sightings data, photographs of Risso’s dolphins from northeast Scotland and the Northern Isles were gathered to gain an indication of the presence of the species in this region. A review of all available sighting records from as early as 1933 (n = 1,904 records), showed a historical presence of Risso’s dolphins in the study locations, with a notable increase in sightings reports over time and with higher numbers of sightings reported from July-September. Collation of photographs (n = 1,884) taken by members of the public and researchers facilitated the establishment of two photo-identification catalogues for Northeast Scotland and Orkney (n = 112 individuals) and for Shetland (n = 47 individuals) respectively. Mother/calf pairs were recorded between April and November. Repeated recaptures of identifiable animals throughout the study area provided the first evidence of inter/intra-annual site fidelity. The combined datasets demonstrate the potential importance of inshore coastal waters in northeast Scotland, Orkney, and Shetland as critical habitat for Risso’s dolphins. Recommendations are made for ongoing monitoring studies to inform the protection of Risso’s dolphins in Scottish waters.